Critical Parameters for the Development of Web-Based Knowledge System for Low Volume Rural Roads in Sarawak - Ron Aldrino Chan, Ron Buking; Muhamad Nazri, Borhan; Riza Atiq, Abdullah O. K. Rahmat; Wan Hashim, Wan Ibrahim (Springer, 2020)
Low Volume Rural Roads serve as one of the key infrastructure projects for integrated rural development in Sarawak. This road is important to help promote development, improve the flow of goods and services and ensure good public health and education, as well as land and resource management support. The aim of this study is to identify the critical parameters for the development of a knowledge-based system for the design of Low Volume Rural Roads (LVRRs) in Sarawak. A total of eleven experts with more than 10 years of experience have been selected, particularly in the areas of low-volume road design, construction and planning. The questionnaire and feedback form were used to request knowledge from domain experts. According to the survey, experts agreed that all parameters, namely traffic loading, soil condition, type of terrain, geometric features and drainage, are important for the design of low volume rural roads.